Epvmp: Enhanced Probabilistic Based Vehicular Multi-Hop Strategies Protocol For Crisis In Vanets Broadcasting (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Vehicle-to-Vehicle (V2V) transmission is utilized for most security-related programs targeting Vehicular Ad-hoc Networks (VANETs) to disseminate safety-related knowledge to nearby cars. However, the traditional broadcasting networks have broadcast winds, contributing to intolerable pauses in transmission and loss of packets. This paper proposes an important transmission scheme for distributing protection signals throughout the sensitive region called the Enhanced Probabilistic-based Vehicular Multi-hop Strategies Protocol (EPVMP). Second, by utilizing the index number of a node and other criteria, which are distinct from the current likelihood-based methods, we aim to provide nodes outside the source node with a higher forwarding chance. The parameters may be optimized for a higher likelihood of transmitting performance and preserving the message distribution's necessary efficiency. Second, we suggest a clustering framework such that problems of replication and latency may be substantially decreased. Third, we evaluate the procedure's efficiency, such as the forwarding completion rate, the total number of copies, and the average latency of one jump. Extensive simulation outcomes with substantially increased network efficiency have shown the feasibility of the proposed protocol